Applying Racial Identity Models in Multicultural Counselling - MacDougall, Carol; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
In order to provide competent counselling services to an increasingly diverse clientele in Canada, counsellors must attend to cultural variables in the counselling context. Racial identity models emphasize the assessment of clients' racial identity and its dynamic interaction with counsellors' racial identity. With an emphasis on Helms' (1995) model, this article discusses how racial identity models may be applied to support multicultural counselling practice.